Work Engagement sebagai Mediator Peran Workplace Well-being terhadap Performance pada Karyawan - Faustine, Dea; Zamralita (Psyche 165 Journal, 2024)
The Covid-19 pandemic is a difficult time for everyone all over the world, including companies and their employees. After going through the pandemic, the term new normal emerged. The new normal brings new challenges for companies, especially in the way companies try to retain and attract new employees to work. This situation has an impact on the company, namely that it is difficult to attract and retain employees. One of the things that employees and job seekers need to consider today is workplace well-being. The well-being that employees feel at work plays a role in work engagement. Employees who are committed to their work become more innovative and are willing to put in more effort in carrying out their duties, which is expected to have an impact on performance. To have good performance, one indicator that needs to be considered is the work engagement of employees. Low levels of work engagement can have an impact on reducing employee performance, productivity and motivation. This research aims to determine the role of workplace well-being on performance with work engagement as a mediator for employees at PT X. This research is quantitative research using a questionnaire. The total number of participants was 68 participants and the data was tested using the process macro regression test. For measurement in this study, the workplace well-being questionnaire, individual work performance questionnaire and Utrecht work engagement scale were used. The results of this research show that work engagement is proven to be a full mediation in the role of workplace well-being on performance.